Desain Ergonomi Produk Troli Tabung Gas LPG Berbasis Antropometri dan Voice of Customer Kano - Amelia Rachmi Nasution; Joko Supono (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2026)
ABSTRACT Manual material handling of LPG cylinders in household environments frequently induces musculoskeletal complaints due to the lack of ergonomic assistive tools. This study aims to produce an ergonomic LPG cylinder trolley design based on anthropometric and Kano-method approaches. The trolley is engineered to accommodate cylinders weighing 3 kg to 12 kg and to operate on both flat surfaces and stairways. The anthropometric approach uses hip-height (99th percentile) and hand-width (50th percentile) dimensions to determine handle sizing, while the Kano method identifies user-need attributes and satisfaction levels. Data were collected through questionnaires distributed to 30 respondents and validated using the marginal-homogeneity test. The resulting design is a safe, comfortable, and ergonomic trolley equipped with a hinged-locking support frame, wheel braking system, and a height-adjustable handle finished with anti-slip material. The structure is sturdy and durable, complemented by chrome finishing to enhance aesthetic appeal. The design is expected to reduce awkward-posture exposure and static loading on users when transporting LPG cylinders. Keywords: Anthropometry, LPG Cylinder Trolley, Product Ergonomics, Voice of Customer